A Measure of Monopoly in Selling - Morgan, Theodore (Quarterly Journal of Economics, 1946)
Journal Article A measure of Monopoly in Selling Get access Theodore Morgan Theodore Morgan Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 60, Issue 3, May 1946, Pages 461–463, https://doi.org/10.2307/1880682 Published: 01 May 1946